Service Learning Program: Student Motivation in SMP Negeri 9 Tanjungpinang - Muhammad Rizki; Anoesyirwan Moeins; Fadillah Binti Zaini; Mohd Sharial Bungsu; Ana Haziqah A Rashid; Mas Idayu Saidi; Halimah Mohd Yusof (Lembaga Pengembangan Kinerja Dosen, 2023)
Riau Islands is one of the provinces in Indonesia and has various cultures in it but the most striking is Malay culture and is located on one of the islands, namely Penyengat Island. In addition to having various kinds of Malay cultural historical relics, it also has schools that support children's education on Penyengat Island. One of the schools on Penyengat Island and the object of activity is SMP Negeri 9 Pulau Penyengat. This article will describe the concepts and practices of service learning conducted by Universiti Teknologi Malaysia (UTM) students and students of KKN Luar Negeri STIE Pembangunan Tanjungpinang at SMP Negeri 9 Pulau Penyengat. This learning service aims to provide knowledge about several learnings such as verbal and non-verbal communication, teamwork, and leadership packaged in games involving students of SMP Negeri 9 Pulau Penyengat. This activity was carried out directly at SMP Negeri 9 Pulau Penyengat. The result of this activity is that students of SMP Negeri 9 Pulau Penyengat understand about verbal communication, non-verbal communication, teamwork and leadership.